The political journalism and PR in the communication sphere of society - M. Kh. Alkhazova; L. B. Ezdekova (Современная наука и инновации, 2023)
Scientific reflection on the processes taking place in the political life of societies involves the identification of significant links between journalism and real political reality. The author notes that, in general, the qualitative focus of political journalism contributes to its categorization as a fundamental concept as a political category, as a subject and object of the political process.It is concluded that political journalism is a broad branch of journalism that includes coverage of all aspects of politics, political processes and political science, including political PR. It is emphasized that political journalism, including PR, is carried out in all types of mass media. At the same time, political journalism is the widest field of journalism, and its subject area can be any sphere of not only political, but also social life – from political PR to disputes and discussions on the topic of disqualification of athletes at international championships and directly political life itself at different levels of society functioning. It is proved that the main direction of political journalism is political ideas, PR activities in the field of political and building political guidelines of society.